Transcortical selective amygdalohippocampectomy for intractable mesial temporal lobe epilepsy: a review of outcomes in a single center - Bintoro, Aris Catur; Arifin, Muhamad Thohar; Harsono, Harsono; Husni, Amin; Brilliantika, Surya Pratama; Bakhtiar, Yuriz; Khairunnis, Novita Ikbar; Askoro, Rofat; Bunyamin, Jacob; Hadisapurto, Soeharyo; Muttaqin, Zainal (Sanglah General Hospital, 2022)
Introduction: Various surgical procedures have been found to effectively treat intractable temporal lobe epilepsy (TLE), including transcortical selective amygdalohippocampectomy (SAH), which is intended to protect the temporal lobe and to prevent interference with vascular structure. This research analyzed the outcome of post-operative seizure-free with transcortical selective amygdalohippocampectomy for intractable mesial temporal lobe epilepsy patients in a minimum two-year follow-up after surgery. Methods: Data of one hundred ninety-two patients who had undergone transcortical selective amygdalohippocampectomy for non-lesional, medically intractable, temporal lobe epilepsy were analyzed. Result: The statistical analysis indicated that Focal to Bilateral Tonic-Clonic Seizure had a more significant outcome (p=0.019) than other seizures. In all research subjects, after three, six, and twelve years of follow-up, the chance for a seizure-free after surgery was respectively 93.2 percent, 67.9 percent, and 36.7 percent with a median average survival period for all subjects of 11.00 years (95 % CI: 8.55 – 13.44) Conclusions: Transcortical selective amygdalohippocampectomy is an effective therapy for intractable mesial temporal lobe epilepsy and provides a satisfactory outcome. The transcortical approach allows an appropriate operative field by careful dissection with limited retraction to eliminate the epileptogenic target while preventing damage to the underlying vascular and cortical structures.